Histopathological Spectrum of Neoplastic Lesions of Female Reproductive System at a Tertiary Care Hospital in Bharatpur, Chitwan - Sedhain, Mamata; Pathak, Priya; Goyal, Binita; Subedi, Pratigya (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Malignant neoplasms of the female genital tract accounts for majority of the cancers in females. The incidence and pattern of malignancies vary from region to region due to differences in genetic patterns, lifestyle and sociocultural factors. The objective of this research is to study the histopathological spectrum of neoplastic lesions of female reproductive system. Methods A total of 309 samples of neoplastic lesions were included in the study from the period of January 2017 to December 2021. Results Most of the neoplastic lesions were found in the uterine corpus, followed by ovary, breasts, cervix and vulva. 80.25% of the neoplastic lesions were benign and 11.97% were malignant; the rest being premalignant and borderline categories. Conclusions Malignant neoplasms of female genital tract contributes to major cancer burden among women and therefore special measures should be adopted to reduce its incidence and improve the prognosis